Trinuclear copper(ii) pyrazolate compounds: a long story of serendipitous discoveries and rational design. Issue 13 (16th February 2017) - Pandolfo, Luciano; Pettinari, Claudio
Abstract : The ease of obtaining the triangular Cu3 (μ3 -OH)(μ-pz)3 moiety (pz = pyrazolate), and its supramolecular self-assemblies, uses and perspectives are reviewed. Abstract : In the past decade great effort has been put into the development of synthetic strategies to produce trinuclear triangular Cu II (TTC) arrays, which may be synthetic analogues of the trinuclear site in ascorbate oxidase and blue oxidase. A large number of scientific contributions have been dedicated to the synthesis and spectroscopic characterization of TTC arrays. In contrast, only a small number of studies deal with their possible applications. As a consequence, systematic studies describing their reactivity are very rare and the few existing models can only partially explain how structural and molecular parameters influence their reactivity and their possible uses and applications. This contribution reports a summary of all experimental results related to the Cu3 (μ3 -OH)(μ-pz)3 core (pz = unsubstituted pyrazolate). We describe here all species, distinguishing them according to whether they are neutral, cationic or anionic, as well as their main structural features, the synthetic procedures employed for their production, their reactivity toward nucleophiles and strong acids and, finally, their possible and perspective applications.